Painting of Treasure Island (J.C. Bardell)
Structural pageantry that combines the most thrilling features of color and architecture in the Occident and the Orient, will be seen at the Golden Gate International Exposition on the world's largest man-made island on San Francisco Bay. Terminus of the mile-long main esplanade of the Fair is the Court of the Hemispheres, with its imposing gateway to the Theatre of the Sky. Brilliant-hued murals, walls in golden designs, waving banners and giant globes that reveal the continents in colored relief, will surround the fountains and gardens of the court.